Responses to single and multiple temperature-, medium-, and pH-stimuli triggering reversible shape shifts in hydrogel actuators. (January 2023) - Wang, X.; Behl, M.; Lendlein, A.; Balk, M.
Graphical abstract: Highlights: Hydrogel actuators providing modulated swelling induced by medium- and pH-changes were designed. Coupled functionalities of actuation and modulated swelling result in a conditioned actuation behavior. Repeated application of temperature changes in ethanol or at another pH value leads to the suppression of actuation functionality. Abstract: Adaptivity is an essential capability of creatures to develop skills for surviving and reproducing. Mimicking such behavior would enable the design of biologically inspired functions. Hydrogel actuators are promising candidate materials capable of stimuli-responsive movements via water uptake and release. Here, for the first time, the adaptive-like movement of reprogrammable hydrogel actuators is demonstrated by integrating two independent functions: a temperature-triggered actuation and a medium- and pH-based modulated swelling, into one multiphase network. Reversible crystallization of poly( ε -caprolactone) (PCL) provided bending movements up to 71° (realized by temperature changes between 5 °C and 40 °C). Changing solvent from water to ethanol increased swellability up to 240 vol%. Bending angles decreased by 32° as some PCL fractions are dissolved in ethanol and cannot participate in the crystallization-induced elongation guiding the movement. When the actuators were modified with acrylic acid moieties, a modulated swelling between 270 vol% at pH = 13 and 130 vol% at pH = 1 was achieved. The resulting swelling/deswelling response induced reversible bending movements up to 54°. In consequence, the coupled functionalities (actuation and modulated swelling) resulted in conditioned actuation behavior as an intermediate feature between stimuli-sensitivity and adaptivity.